(untitled) (Forum Penelitian Agro Ekonomi, 2016)
The Beef Self-Sufficiency Program (PSDS) to be realized in 2014 is one of the main agricultural development targets for the period of 2010-2014. Some regulations are launched to support this program. Many provincial governments create program to encourage domestic cattle population. Artificial insemination (AI) is still a dominant method besides natural reproduction through the village breeding centers (VBC). Supply of quality frozen cement at sufficient quantity and affordable price, expanding number of inseminators, improving VBC, profitable domestic cows’ price, feed supply, and grazing land intensification are prerequisites for beef self-sufficiency achievement.